ISOLATION OF PHAGES FOR CANDIDA INHIBITION AND INCREASING EFFICIENCY OF ANTIFUNGAL AGENTS WITH THEM - Panicker, Suneeta; Patil, Samrudhi; Peshwe, Samrudhi; Kale, Sanika (Journal of Global Pharma Technology, 2024)
Objectives: Most of the fungal infections are caused by Candida sp. The five prominent species of Candida which are involved in these infections are Candida albicans, Candida glabrata, Candida krusei, Candida tropicalis and Candida dublinienesis. Generally, echinocandin, ketoconazole fluconazole, amphotericin B are recommended to treat Candida infections. But, these infections are often complicated by resistance or refractoriness to current antimicrobial agents. The resistance to azole is most prominent, especially in C. albicans and C. dublinienesis. Therefore, an urgent need exists for new therapeutic strategies based on the identification of new microbial targets and novel antimicrobial agents. One such hypothetical therapeutic strategy may involve the use of mycoviruses that are able to selectively infect fungi. Methods: Candida was isolated from clinical samples. Phages against Pseudomonas were isolates and then checked the antifungal efficiency of these phages by double overlay agar method. Efficiency of these phages with the known antifungal agent (ketoconazole) was determined.Results: The phages of Pseudomonas were found to be effective against the Candida sp. Incorporation of isolated phages into antifungal agent increased its efficiency. These isolated phages can be used in various medicinal products like intimate hygiene, antifungal creams, etc. Conclusion: There are not many reports on bacterial phages against fungus pathogens hence such primitive investigations can aggravate researchers across the global to think innovatively on the similar lines and research to the molecular levels. Keywords: Candidiasis, Biofilm, Morphology switching, Azole resistance, Pseudomonas phages, Antifungal creams.